Rekayasa Bahan Bangunan dari Abu Vulkanik sebagai Alternatif Semen Ramah Lingkungan - Edi Priyono; Mettadewi Wong (Journal of New Trends in Sciences, 2025)
This study aims to analyze the effect of body angle variations on propulsion force and water resistance in swimmers through a biomechanical approach. This research is motivated by the importance of movement efficiency in swimming, where suboptimal body positions can increase drag coefficient, thus slowing down swimming speed. The method used is a quantitative experimental design, involving professional and semi-professional swimmers. Instruments used include a motion capture system to record body movements, force sensors to measure propulsion and water resistance, and biomechanical software to analyze force vectors and drag coefficient. The results show a significant difference in swimming performance based on body angle variations. At a 0° angle, the average propulsion force is 145.3 N with a drag coefficient of 0.92. At a 15° angle, the propulsion force increases to 162.7 N with the lowest drag coefficient of 0.78. Meanwhile, at a 30° angle, the propulsion force decreases to 150.1 N, and the drag coefficient increases to 0.88. These findings indicate that a 15° body angle is the most optimal position, as it minimizes water resistance and maximizes propulsion force, thus improving swimming movement efficiency. The implications of this study suggest that biomechanical approaches can be used to design more efficient swimming training programs. The findings are also beneficial for swimmers and coaches in developing more effective training strategies.